Case study of sinonasal cavernous haemangioma manifesting as recurrent nose bleeds with a literature review - Mane, Balaji Shankarrao; Gavali, Rushali Madhukar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Cavernous hemangiomas are relatively uncommon, primarily found in adults, particularly women. These tumors frequently present with unilateral nosebleeds and nasal blockage. Furthermore, there are only a few recorded instances of cavernous hemangiomas originating from the maxillary sinus in medical literature. This case report has been written because of the rare occurrence of cavernous hemangioma in the paranasal sinus. We present a case of a cavernous haemangioma located in the right maxillary sinus of a 30-year-old male. During an anterior rhinoscopy, a large necrotic tumor was observed, which bled upon contact and obstructed the right nasal cavity. A preoperative endoscopic biopsy was conducted on the mass to eliminate the possibility of cancer, but the findings were inconclusive. A CT scan displayed a mass occupying the entire right maxillary sinus and extending into the right nasal cavity, as well as reaching the ethmoid sinuses and choana, without any evidence of bone damage or displacement of the nasal septum. The Intraoperative frozen-section pathology showed that the respiratory epithelium displayed considerable haemorrhage, necrosis, inflammation, and edema, as well as the growth of blood vessels of different sizes. For our patient, the minimally invasive transnasal endoscopic approach was successful with minimal bleeding. The tumor was completely excised, and during the one-year follow-up, the patient has not experienced any recurrence. However, the final biopsy of the lesion confirmed that it was a cavernous hemangioma.